Obstetric outcomes in pregnancies with normal nuchal translucency and abnormal ductus venosus Doppler in the first trimester ultrasonography. (18th May 2016) - Seckin, K. D.; Karslı, M. F.; Baser, E.; Yeral, M. I.; Tasin, C.; Ozgu Erdinc, A. S.; Danisman, N.
Abstract : In the present case–control study, we evaluated obstetric outcomes of pregnancies with normal nuchal translucency (NT) and abnormal ductus venosus (DV) Doppler findings in the first trimester combined screening test for chromosomal abnormalities. All study patients underwent DV Doppler examination, concurrent with the combined screening test. DV Doppler revealed pathologic findings in 14 pregnant women despite normal NT after the elimination of lost to follow-up and foetal anomaly. Obstetric outcomes of the case patients were compared with a control group that were matched for mean gestational age, and Crown–rump length with normal NT and DV Doppler measurements was selected comprising 88 pregnant women. Regarding maternal outcomes, women with abnormal DV Doppler findings had a higher rate of placental abruption, delivered at an earlier mean gestational age (preterm delivery). Interestingly, a higher rate of spontaneous vaginal delivery rate was observed in these patients. From the foetal perspective, pregnancies with abnormal DV Doppler had lower birth weight and received lower Apgar scores. In conclusion, an abnormal DV Doppler test in the first trimester was associated with poor maternal and foetal obstetric outcomes. These findings should be elucidated in future studies.